2018
DOI: 10.4103/atm.atm_304_17
|View full text |Cite
|
Sign up to set email alerts
|

Primary pulmonary lymphoepithelioma-like carcinoma in Singapore

Abstract: BACKGROUND:Primary pulmonary lymphoepithelioma-like carcinoma (PPLELC) is a rare subtype of nonsmall cell lung cancer (NSCLC) predominantly reported in East Asia. We aimed to evaluate clinical characteristics, diagnosis, treatment, and prognosis of PPLELC in Singapore.METHODS:Retrospective review of all patients diagnosed with PPLELC at our center between 2000 and 2014.RESULTS:All 28 patients were Chinese, 67.9% were female, and the median age was 58 years (range37–76 years). Majority (89.3%) were never smoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In our study, the patients with LELC and SCLC exhibited some characteristic clinical features, which are consistent with the findings of previous studies. First, SCLC was significantly more prevalent among male patients, 11 , 15 , 22 whereas LELC was significantly more prevalent among nonsmoking and female patients. 4 , 12 , 29 Second, compared with patients with SCLC, patients with LELC were frequently diagnosed at younger ages.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our study, the patients with LELC and SCLC exhibited some characteristic clinical features, which are consistent with the findings of previous studies. First, SCLC was significantly more prevalent among male patients, 11 , 15 , 22 whereas LELC was significantly more prevalent among nonsmoking and female patients. 4 , 12 , 29 Second, compared with patients with SCLC, patients with LELC were frequently diagnosed at younger ages.…”
Section: Discussionmentioning
confidence: 95%
“… 3 Larger series of LELC have mostly been reported in East Asia, particularly in southern China, 1 , 4 7 Taiwan, 8 , 9 Hong Kong, 10 and Singapore. 11 The common manifestations of LELC on computed tomography (CT) scans include a tumor with homogeneous enhancement and the presence of lymphadenopathy, and late-staged lesions of LELC are often centrally situated in the lungs while early-stage tumors are often located peripherally. 2 , 6 , 10 , 12 , 13 The prognosis of patients with pulmonary LELC is more favorable than that of patients with non-LELC NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…The overall survival rate for patients with advanced LELC is low. Tay et al [ 28 ] reported 5-year survival rates for advanced stage patients with PLELC in Singapore as less than 10%. Combination therapy is the best option to achieve the best possible outcome.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that patients with PLELC have a better prognosis than those having other types of non-small cell lung cancer (NSCLC) [3]. However, the prognosis of stage IV-PLELC is not better than that of NSCLC [9, 10]. As to the treatment for PLELC, complete resection is the primary approach to obtain a cure, but treatment for advanced PLELC is controversial, owing to its being a rare entity [3].…”
Section: Discussionmentioning
confidence: 99%